Monogenic disorders as mimics of juvenile idiopathic arthritis - Laura Furness; Phil Riley; Neville Wright; Siddharth Banka; Stephen Eyre; Adam Jackson; Tracy A. Briggs (BMC, 2022)
Abstract Background Juvenile idiopathic arthritis is the most common chronic rheumatic disease of childhood. The term JIA encompasses a heterogenous group of diseases. The variability in phenotype of patients affected by the disease means it is not uncommon for mimics of JIA to be misdiagnosed. Case presentation We present four cases who were treated in single tertiary rheumatology centre for JIA who were subsequently diagnosed with a rare monogenic disease. All four patients shared the unifying features of presenting in early childhood and subsequently suffered with refractory disease, not amenable to usual standards of treatment. Multicentric Carpotarsal Osteolysis Syndrome and Camptodactyly-arthropathy-coxa vara-pericarditis syndrome are non-inflammatory conditions and patients typically present with arthropathy, normal inflammatory markers and atypical radiological features. Blau syndrome is an autosomal dominant condition and patients will typically have symmetrical joint involvement with a strong family history of arthritis, signifying the genetic aetiology. Conclusions We share our learning from these cases to add to the growing portfolio of JIA mimics and to highlight when to consider an alternative diagnosis. In cases of refractory disease and diagnostic uncertainty further imaging and genetic testing can play a crucial role in establishing the aetiology. In all of these cases the correct diagnosis was made due to careful, longitudinal clinical phenotyping and a close working relationship between rheumatology, radiology and clinical genetics; highlighting the importance of the multidisciplinary team in managing complex patients.